Armenia : Diagnostic Review of Consumer Protection and Financial Literacy, Volume 2. Comparison with Good Practices - World Bank (Washington, DC, 2013)
The objectives of the diagnostic review of consumer protection and financial literacy for Armenia are: (i) to assess the existing financial consumer protection framework, by reviewing laws, regulations and practices in Armenia compared to international good practices; and (ii) to provide recommendations on ways to improve consumer protection and financial literacy in Armenia. The review provides a detailed assessment of the institutional, legal and regulatory framework in four financial segments, namely banking, non-bank credit institutions, securities, and insurance. Many key steps have already been taken in financial consumer protection, especially at the regulatory and institutional levels. Regarding the institutional framework, adequate resources need to be allocated to the consumer protection team and modern supervisory tools should be made available. Consumer organizations should be strengthened and motivated to assist the Central Bank of Armenia (CBA) in market monitoring. In terms of consumer disclosure, the CBA should issue regulations that require financial institutions to provide clear, understandable, timely, comparable and standardized information to consumers. In the area of regulation of business practices, the CBA should require that sales agents are well trained and should test them regularly. All financial institutions should regularly analyze the complaints received and the analysis should be provided to the CBA. The Steering Committee for the National Strategy of Financial Education should become the key body to manage financial education in Armenia.